(untitled) (Journal of Pharma Insights and Research, 2025)
Mimosa pudica L., a neotropical native plant, is now a pantropical species renowned for its rapid thigmonastic (touch-induced) leaf movement. Beyond this well-known curiosity, it possesses a deep-rooted history in traditional medicine systems, including Ayurveda and Unani, where it is utilized for a spectrum of ailments such as gastrointestinal disorders, cutaneous wounds, inflammation, and urogenital complaints. The ethnomedical applications of the plant are supported by its complex phytochemical profile, which is rich in secondary metabolites. The main constituents include the toxic non-protein amino acid mimosine, various C-glycosylflavonoids, tannins, terpenoids, and other phenolic compounds. These bioactive molecules are correlated with a wide array of scientifically validated pharmacological properties. Preclinical investigations have demonstrated significant antimicrobial, antioxidant, anti-inflammatory, wound healing, antidiabetic, hepatoprotective, and diuretic activities. For example, extracts have shown efficacy in alloxan-induced diabetic models and protection against carbon tetrachloride-induced hepatotoxicity. The dual identity of this plant as a valuable medicinal resource and a problematic invasive weed in agricultural regions presents a complex ecological profile. This review correlates the current scientific knowledge on M. pudica, linking its traditional uses to its characterized phytochemicals and documented biological activities.